STATE AND TRENDS OF THE DEVELOPMENT OF BIOECONOMIC-ORIENTED LIVELIHOOD PRACTICES - B. Stoykova; Y. Yarkova; N. Markov (Trakia Journal of Sciences)
The aim of the present study is to establish the extent to which natural resources are used and how traditional livelihood practices are exercised at a regional level. The object of this study is a region with developed mass tourism - Bansko Municipality. The subject addresses traditional livelihood practices and the opportunities for expanding alternative forms of tourism. The revival of traditional livelihood models, which directly corresponds to current trends in bioeconomy, can make alternative forms of tourism an important part of the local development strategies in the forthcoming programming period after 2020, including regions established as mass tourism ones. The study has been conducted by applying the survey method in the municipality of Bansko in the period of February-March 2020 coinciding with the onset of the epidemic situation related to COVID-19 in Bulgaria. Taking into account the results from the survey, it is possible to draw conclusions about the extent to which certain conditions for the development of alternative forms of tourism have been created when facing new challenges.